MEMBANGUN MODEL BISNIS BERKELANJUTAN DENGAN MENERAPKAN SISTEM INFORMASI MANAJEMEN YANG RAMAH LINGKUNGAN - Sri Rapida; Muhammad Irwan Padli Nasution (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
Climate change and environmental degradation are pressing global issues. Business, As one of the main actors in human activities, has an important role in addressing These issues. This article discusses building a sustainable business model by Implementing an environmentally friendly management information system (SIM). Through descriptive methodology, this research analyzes various aspects, from the Definition of a sustainable business model and the role of SIM in supporting Sustainability, to how SIM can be designed and implemented to minimize Environmental impacts and drive operational efficiency